At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
The answer is x=-6, x=8
Step-by-step explanation:
I recommend using the quadratic formula to solve this problem.
x^2=a
-2x=b
-48=c
Plug it into the quadratic formula.
New equation:[tex]\frac{2+-\sqrt{(-2)^2-4(1)(-48)}}{2(1)}[/tex]
Simplify
Equation: [tex]\frac{2+-\sqrt{4+192}}{2}[/tex]
Add 4 and 192.
Equation: [tex]\frac{2+-\sqrt{196}}{2}[/tex]
Do the square root of 196.
Equation: [tex]\frac{2+-14}{2}[/tex]
Make into two different equations.
Equation 1: [tex]\frac{2+14}{2}[/tex]
Equation 2: [tex]\frac{2-14}{2}[/tex]
Solve the two equations and you will get -6 and 8. Hope this helps!
[tex] \huge \boxed{\mathbb{QUESTION} \downarrow}[/tex]
- Solve using the quadratic formula ⇨ x² - 2x - 48 = 0.
[tex] \large \boxed{\mathbb{ANSWER \: WITH \: EXPLANATION} \downarrow}[/tex]
[tex] \sf \: x ^ { 2 } - 2 x - 48 = 0[/tex]
All equations of the form ax² + bx + c = 0 can be solved using the quadratic formula: [tex]\sf \frac{-b±\sqrt{b^{2}-4ac}}{2a}[/tex]. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
[tex] \sf \: x^{2}-2x-48=0 [/tex]
This equation is in standard form: ax² + bx + c = 0 Substitute 1 for a, -2 for b and -48 for c in the quadratic formula.
[tex] \sf \: x=\frac{-\left(-2\right)±\sqrt{\left(-2\right)^{2}-4\left(-48\right)}}{2} \\ [/tex]
Square -2.
[tex] \sf \: x=\frac{-\left(-2\right)±\sqrt{4-4\left(-48\right)}}{2} \\ [/tex]
Multiply -4 times -48.
[tex] \sf \: x=\frac{-\left(-2\right)±\sqrt{4+192}}{2} \\ [/tex]
Add 4 to 192.
[tex] \sf \: x=\frac{-\left(-2\right)±\sqrt{196}}{2} \\ [/tex]
Take the square root of 196.
[tex] \sf \: x=\frac{-\left(-2\right)±14}{2} \\ [/tex]
The opposite of -2 is 2.
[tex] \sf \: x=\frac{2±14}{2} \\ [/tex]
Now solve the equation [tex]\sf\:x=\frac{2±14}{2}[/tex] when ± is plus. Add 2 to 14.
[tex] \sf \: x=\frac{16}{2} \\ [/tex]
Divide 16 by 2.
[tex] \boxed{ \boxed{ \bf \: x=8 }}[/tex]
Now solve the equation [tex]\sf\:x=\frac{2±14}{2} [/tex] when ± is minus. Subtract 14 from 2.
[tex] \sf \: x=\frac{-12}{2} \\ [/tex]
Divide -12 by 2.
[tex] \boxed{\boxed{ \bf \: x=-6 }}[/tex]
The equation is now solved.
[tex] \underline{ \bf \: x=8 }\\ \underline{ \bf \: x=-6 }[/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.